PEMBAJAKAN MEREK DALAM TATANAN HUKUM KEKAYAAN INTELEKTUAL DI INDONESIA: KRAFT FOODS GLOBAL BRANDS LLC., (OREO) MELAWAN PT. SIANTAR TOP Tbk (ORIORIO) - Robiatul Adawiyah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Trademarks are part of intellectual property rights, for this reason, there is a need for legal protection over trademarks. The current phenomenon is that there is a lot of counterfeiting or piracy of brands which of course has violated the law carried out by producers of goods and/or services that do not have good faith. Based on the case, this research aims to find out the legal policies related to brands in the intellectual property legal order in Indonesia and to determine the effects of brand piracy on the Indonesian economy. This research is doctrinal research using normative legal research methods. The approach used is the legislation approach and conceptual approach by prioritizing primary, secondary and tertiary legal materials such as binding regulations, books, and journals of legal research related to brands. This study shows that brand-related policies are regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications and their implementing regulations. The rights to the mark are granted by the state through the registration mechanism which must be carried out by the owner. The registration is mandatory so that if rights are not registered the trademark will not be protected. Then the economic impact on brand piracy is the loss of brand owners, consumers, and the state. Brand owners suffer losses because their products cannot compete with pirated brands whose prices are relatively cheaper. Whereas the state does not get income from sales tax. In the case of taxation, it is a significant source of state revenue to finance development. As a result of brand piracy also caused capital flight abroad (capital flight), which affected the number of unemployed.